Hydrophobic Membrane Wettability: Effects of Salinity and Temperature - Orhan Kaya (Membranes)
In this study, molecular dynamics (MD) simulations were used to investigate the effects of salinity (NaCl) and temperature (25 °C and 80 °C) on the wettability of droplets on a realistically modeled hydrophobic PTFE (polytetrafluoroethylene) surface. Droplet sizes of 20, 25, and 30 nm were analyzed using both pure water and 8.45% NaCl solutions. The results indicated that salinity increased the contact angles, strengthening the PTFE’s hydrophobicity by disrupting the water’s hydrogen bonding at the interface and reducing the spreading area. Higher temperatures also led to an increase in contact angles by decreasing water structuring, although this effect was less pronounced than that of salinity. Ion concentration analysis revealed that a significant number of ions migrated away from the PTFE surface, a phenomenon further clarified through radial distribution function (RDF) analysis.